Efficiency Evaluation on the Influence of Washing Methods for Biodiesel Produced from High Free Fatty Acid Waste Vegetable Oils through Selected Quality Parameters - Ortiz Lechuga, Eugenia Guadalupe; Rodríguez Zúñiga, Mauro; Arévalo Niño, Katiushka (2020)
The increasing use of alternative energy sources has brought benefits like the recycling of waste vegetable oils (WVO) for biodiesel production; however, this practice presents challenges derived from a highly variable raw matter. Our research focused on the washing techniques usually employed by small to medium scale producers which may lack the infrastructure to perform high-grade purification and often relay on the employment of “artisanal” technology. We report biodiesel production from pure canola oil (C1) and a mix of soybean/canola oil (C2) as well as WVO from sample C2 with high free fatty acid content (2.7 FFA %) oil. We selected seven quality tests: pH determination, cloud, pour and flash point, acid number (AN), water/sediments and soap content considering the most commonly failed checkpoints in biodiesel production. From the use of four washing techniques, we determined that the sawdust filtration had the highest recovering yield with 89%. The majority of the washed biodiesel met the America Society of Testing Material (ASTM) standard limits for the tests selected. Biodiesel stability was tested from week 0 to week 6, determining a shelf life of three weeks in optimal conditions without the addition of antioxidants or specific storage conditions.